PERIODE KRITIS TANAMAN BAWANG MERAH VARIETAS BIMA (Allium ascalonicum L.) TERHADAP PERSAINGAN GULMA - Muhammad Ghufron Abdillah; Agus Mulyadi Purnawanto; Gayuh Prasetyo Budi (Universitas Muhammadiyah Purwokerto, 2016)
The weed throughout the life cycle of crops doesn’t give negative impact as always. The survival period of crops which is very sensitive toward weeds is called by critical period. This study aims to determine the critical period of Bima onion (Allium ascalonicum L.) towardweeds. The research was conducted in Dukuhwaluh, Kembaran, Banyumas regency, from February to June 2016.Research compiled in a randomized completely block design. Factors studied were eight treatment levels namely G0 : clean weeding on 0–60 dap, G1 : clean weeding on 0–20 dap, G2 : clean weeding on 20–40 dap, G3 : clean weeding on 40–60 dap, G4 : clean weedingon 0–20 dap and 40–60 dap, G5 : clean weeding on 0–40 dap, G6 : clean weeding on 20–60 dap, dan G7 : clean weeding on 0–60 dap was repeated 4 times. The variables measured were leaf length, leaf number, the number of bulbs, tubers fresh weight per hill, tuber dry weightper hill, tuber diameter, and the total dominance of weeds.The results showed the competition period of weeds affect the growth and yield of Bima Onion (Allium ascalonicum L.), a critical period of this onion occurred on 20-40 dap. The dominant weeds grew in onion during this study was Cyperus imbricatus, Cyperus kyllingia,and Cyperus rotundus. Weeding session of this Bima onion will be efficiently implemented at age 20-40 dap to prevent yield loss.